2013
DOI: 10.1186/1471-2164-14-517
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of peanut gynophores revealed global reprogramming of gene expression during early pod development in darkness

Abstract: BackgroundAfter the zygote divides few times, the development of peanut pre-globular embryo and fruit is arrested under white or red light. Embryo development could be resumed in dark condition after gynophore is buried in soil. It is interesting to study the mechanisms of gynophore development and pod formation in peanut.ResultsIn this study, transcriptome analysis of peanut gynophore was performed using Illumina HiSeq™ 2000 to understand the mechanisms of geocarpy. More than 13 million short sequences were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 42 publications
3
67
0
Order By: Relevance
“…Cloning and characterization of peanut WOX13 subfamily genes Three WOX13 subfamily gene cDNAs were identified from peanut transcriptome data (BioProject: PRJNA181974) (Xia et al 2013) and named as AhWOX13A, AhWOX13B1, and AhWOX13B2. WOX13A contains an ORF of 630 bp, encoding a 209 amino acid polypeptide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning and characterization of peanut WOX13 subfamily genes Three WOX13 subfamily gene cDNAs were identified from peanut transcriptome data (BioProject: PRJNA181974) (Xia et al 2013) and named as AhWOX13A, AhWOX13B1, and AhWOX13B2. WOX13A contains an ORF of 630 bp, encoding a 209 amino acid polypeptide.…”
Section: Resultsmentioning
confidence: 99%
“…Cultivated peanut is allotetraploid (AABB, 4n=4x=40) which originated from a single hybridization event between AA and BB wild species and subsequently underwent spontaneous genome duplication (Stalker and Simpson 1995;Moretzsohn et al 2013;Kochert et al 1996;Ferguson et al 2005;Freitas et al 2007;Gregory and Gregory 1979;Hammons 1982;Knauft and Gorbet 1995). Peanut gynophore is a specialized and unique organ that carries and eventually pushes the fertilized ovules into the soil in order for seed and fruit development to occur (Xia et al 2013;Moctezuma 2003). The peanut gynophore has a typical shoot anatomy and responds positively to gravity, similar to a typical primary root (Moctezuma and Feldman 1998;Moctezuma and Feldman 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut pod swelling is a complicated process that is controlled by several plant hormones, such as auxin, GA, ethylene, and abscisic acid (Xia et al, 2013). Previous studies have shown that AtSPL3 and AtSPL8 affect endogenous GA levels and signaling in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Peanut is an important global oil crop and protein source. Peanut plant flowers and finishes pollination above ground as do other plants, while the ovule-carrying peg (gynophore) starts to form above ground and then grows downwards to bury the fertilized ovule in the soil for pod development (Thompson et al, 1985;Xia et al, 2013;Zhu et al, 2014). In this study, we identified 15 potential peanut SPLs that all contained a conserved SBP domain.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2013) took advantage of available transcriptome data to detect two cell-aging transcripts that significantly increased in the late stage of unburied gynophores and may participate in the abortion of gynophores on the ground. Xia et al (2013) found that a series of transcripts, including endogenous hormones, respond to optical signals, and that morphogenesis and cell division pathway transcripts showed distinct changes before and after the burying of the gynophore. Zhu et al (2014) compared the transcriptome of the gynophore before and after burying, and described the relevance of changes in expression and hormone levels of GA, IAA, and other hormone-related transcripts.…”
Section: Introductionmentioning
confidence: 99%